Molecular characterization of Flavobacterium spp. isolated from Rainbow trout (Oncorhynchus mykiss) farmed in Southern Africa and development of a PCR-based tool for differentiating between isolates - Komane, Godfrey M (Department of Molecular and Cell Biology, 2022)
Bacterial fish diseases caused by yellow-pigmented, filamentous bacteria of the genus Flavobacterium are among those that lead to significant losses in the international aquaculture industry. An increasing number of Flavobacterium spp. have been isolated in association with diseased fish within the aquaculture industry. In salmonids, well known flavobacterial diseases include bacterial cold-water disease (F. psychrophilum), rainbow trout fry syndrome (F. psychrophilum), bacterial gill disease (F. branchiophilum, F. aquatile), and columnaris disease (F. columnare). Conventional diagnosis of Flavobacterium spp. is based on physico-chemical tests, but these tests are time-consuming and labor-intensive, and they are unable to distinguish between closely related species due to morphological similarities. Furthermore, little information exists on the diversity of fish associated Flavobacterium spp. from southern Africa. Recently, numerous, yellow-pigmented, filamentous bacteria were isolated from diseased rainbow trout farmed in South Africa and neighboring Lesotho. The aim of the present study was to elucidate the genotypic and phylogenetic diversity of the Flavobacterium spp. associated with these fish and to develop a new molecular system for rapid and accurate identification and differentiation of the isolates. In order to do this, the genotypic and phylogenetic diversity of ninety bacterial isolates, mostly yellow-pigmented, obtained from the gills, skin ulcers, liver, and kidneys of diseased Oncorhynchus mykiss was assessed following PCR and sequencing of the 16S rRNA gene. A BLAST search of the GenBank database revealed that 47 of the 16S rRNA gene sequences showed high similarity to several Flavobacterium spp.; 6 showed high similarity to Chryseobacterium spp., and 19 non-Flavobacterium isolates were identified, which included, amongst others, Hafnia spp. and Aeromonas spp. Fifteen isolates were excluded from further analysis due to poor DNA sequence data, whilst four isolates showed high similarity to uncultured bacteria and they were also excluded from further analysis. Isolate OM-46 was excluded from the phylogenetic analysis of Flavobacterium spp. since only the forward 16S rRNA sequence was available. Phylogenetic analysis based on the maximum likelihood method confirmed the allocation of 46 isolates as Flavobacterium spp., and 6 isolates as Chryseobacterium spp. Differential identification of the Flavobacterium spp. was achieved following PCR amplification of a hypervariable region of the 16S rRNA gene followed by high-resolution melt (HRM) analysis. Nine Flavobacterium isolates, presumed to be different species based on the phylogenetic analysis were identified and successfully differentiated using high resolution melt analysis. The present study has identified new Flavobacterium spp. (OM-13, OM-39, OM-51, OM-82, and OM84) from rainbow trout farmed in southern Africa and developed a tool that may be useful for the management of flavobacterial diseases worldwide.